AKUNTABILITAS PENGELOAAN ALOKASI DANA DESA (ADD) TAHUN 2017 DI KABUPATEN BREBES - Andri Widianto; Erni Unggul Sedya Utami; Ririh Sri Harjanti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The granting of Village Fund Allocation is intended to support Village Government programs and activities in the fields of Government, development and empowerment.This study provides an overview of the accountability of the village fund allocation management system in the area of Brebes. Data Collection Technique conducted in this research is Interview. Data analysis uses the thinking of Miles and Huberman (2014) in (Kholmi, 2016) namely interactive model data analysis. The results of this study indicate that the stages of Planning, Implementation, Accountability and Supervision are in accordance with the Regulations Keywords: Accountability, Village Fund Allocation